Clases magistrales en carreras de la salud: reflexiones basadas en evidencias y experiencias - Millán K., Teresa; Vargas C., Nelson A. (Revista Hospital Clínico Universidad de Chile, 2009)
Based on findings and conclusions of two former studies on the subject, carried out with students and academic staff of the Faculty of Medicine at the University of Chile, as well as an international review of the pertinent literature, the contribution, advantages and disadvantages of lectures in health careers training and learning is analyzed. Within this frame of reference, a set of recommendations to improve lectures effects is offered and analyzed through the authors experience and reflections upon students and teachers data, after a span of almost ten years of use.